EPIDEMI PENYAKIT BUSUK PANGKAL BATANG LADA PADA KONDISI LINGKUNGAN YANG BERVARIASI - La Ode Santiaji Bande; Bambang Hadisutrisno; Susamto Somowiyarjo; Bambang Hendro Sunarminto (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2015)
Foot rot disease epidemic on black pepper in variety of environmental conditions. The foot rot disease on black pepper caused by Phytophthora capsici Leonian, is often destructive to farmers of black pepper. This research aims to study the infection rate and the pattern of development of the black pepper foot rot disease in various condition of the environment. The research was conducted in the areas of black pepper cultivation in the Ultisol and Entisol soils. In each location plots were set with few (<25%) and abundant (>75%) weeds. Variable observed was disease incidence. The data were used to analyze model of development of the black pepper foot rot disease and infection rate. Results of the research showed that the model of development of the black pepper foot rot disease was not affected by soil type, but the type of soil affected the infection rate. At the pepper plantation with abundance of weeds, the disease development followes Gompertz model. At the plantation with few weeds, however the disease developed in a logistic model. The rate of disease infection on the black pepper plant with abundant weeds lower compared with those with few weeds.